Political Communication Strategy in Winning the Regional Election: A Case Study of the Victory of the ERAMAS Pair in the 2018 North Sumatra Regional Election - Hasibuan, Halim Perdana; Ritonga, Muhammad Husni; Azhar, Anang Anas (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine: 1) The communication strategy of the ERAMAS success team in gaining support in the 2018 simultaneous regional elections in North Sumatra, 2) The campaign communication strategy of the ERAMAS pair in attracting public attention, 3) The obstacles faced by the ERAMAS success team in the 2018 simultaneous regional elections in North Sumatra. This study uses qualitative research with a naturalistic approach, this approach intends to create a systematic and objective description of an event, by collecting, evaluating, verifying, and synthesizing evidence to support facts in order to obtain a conclusion. Data collection in this study was carried out using various observation techniques, interviews, and documentation. The results of the study show that: 1) The communication strategy of the ERAMAS success team in gaining support in the 2018 simultaneous regional elections in North Sumatra is by: a) direct selling, b) involving all elements of society, and c) maximizing the role of social media. 2) The ERAMAS pair's Campaign Communication Strategy in attracting public attention is by: a) being dialogical and open, b) campaigning culturally and structurally, and c) holding religious and social activities. 3) The obstacles faced by the ERAMAS success team in the 2018 simultaneous regional elections in North Sumatra are: a) remote geographical location, b) the many slanders and bad framing, and c) intervention from the central government. Meanwhile, the solutions taken to overcome these obstacles are: a) forming a solid team, b) continuing to campaign politely and obeying the rules, and c) convincing the public by providing the best vision and mission.